Conflict mediation in the school environment: a look at psychology (Research, Society and Development, 2020)
This research aims to understand how mediation positively affects the school community, through the interventions carried out by the professional, making use of the necessary tools to remedy possible conflicting events that may arise from the relationships between students-students, students-teacher, teacher-coordination. The methodology used in the research was a literature review, with data collection carried out between September and October, 2019, in the following databases: Scielo, Pepsic, Google Scholar, Bireme, CAPES journal portal. In the search for articles, the following keywords were used: school violence, conflict mediation, school and family. The results of the research indicate that mediation is an effective way of resolving conflicts in the school environment, as it favors the verbalization and elaboration of conflicts through feelings of understanding, acceptance and solidarity with both parties involved in the conflict. Finally, it is concluded that school violence is a reflection of other violence suffered, such as intrafamily and it is considered that the role of the psychologist as a mediator in the school is an increasingly emerging need to promote the resolution of conflicts that will result in a peaceful school setting.